2020
DOI: 10.1186/s12906-020-03118-9
|View full text |Cite
|
Sign up to set email alerts
|

In vitro anticancer activity of Eclipta alba whole plant extract on colon cancer cell HCT-116

Abstract: Backgrounds Colon cancer is the third most deadly and one of the most diagnosed diseases in the world. Although routine screening and early detection during last decades has improved the survival, colon cancer still claims hundreds of thousands lives each year worldwide. Surgery and chemotherapy is mainstay of current treatment, nevertheless toxicity associated with this treatment underscores the urgency of demand of a better therapeutics. Close to 50% of current chemotherapeutic drugs are direct or indirect d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(39 citation statements)
references
References 28 publications
0
39
0
Order By: Relevance
“…The plant extracts exhibited significant (p < 0.05) cytotoxicity against the cancerous cell, while normal cells (primary lung alveolar and renal primary tubular epithelial cells) appeared less sensitive to plant extracts. Relative much higher cell viabilities for normal cells suggested plant extracts were safe/nontoxic to normal cells [37]. The studies have shown that phenolic-rich extracts of Acer species inhibit cell proliferation in tumor cell lines [38].…”
Section: Anticancer Activitymentioning
confidence: 99%
“…The plant extracts exhibited significant (p < 0.05) cytotoxicity against the cancerous cell, while normal cells (primary lung alveolar and renal primary tubular epithelial cells) appeared less sensitive to plant extracts. Relative much higher cell viabilities for normal cells suggested plant extracts were safe/nontoxic to normal cells [37]. The studies have shown that phenolic-rich extracts of Acer species inhibit cell proliferation in tumor cell lines [38].…”
Section: Anticancer Activitymentioning
confidence: 99%
“…When the cells reached 80% confluence, they were treated with 1‰ dimethyl sulfoxide (DMSO) solution, and 5, 25 50 and 100 μg/mL of esculetin at 37°C for 24 h. The cells were then incubated with 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) (0.5 mg/mL) solution for 4 h, and the resulting formazan was solubilized with 150 μL of DMSO for 30 min. The absorbance of each well was measured at 570 nm, and the absorbance of control cells was considered to indicate 100% cell viability [10,11]. Scheme represented in Fig.…”
Section: Measurement Of Cell Viability By Mtt Assaymentioning
confidence: 99%
“…When the cells reached 80% con uence, they were treated with 1‰ dimethyl sulfoxide (DMSO) solution, and 5, 25 and 50 μg/mL of esculetin at 37 o C for 24 h. The cells were then incubated with 3-(4,5-dimethylthiazol-2-yl)-2,5diphenyltetrazolium bromide (MTT) (0.5 mg/mL) solution for 4h, and the resulting formazan was solubilized with 150 μL of DMSO for 30 min. The absorbance of each well was measured at 570 nm, and the absorbance of control cells was considered to indicate 100% cell viability [10,11].…”
Section: Measurement Of Cell Viability By Mtt Assaymentioning
confidence: 99%